HUBUNGAN MUTU PELAYANAN VCT DENGAN KEPUASAN PASIEN DI PUSKESMAS SIDOMULYO KOTA PEKANBARU - Simanjuntak, Silva Friscilla (Universitas Aufa Royhan, 2022)
Voluntary Counseling and Testing (VCT) is a process of voluntary counseling and HIV testing on the initiative of the individual concerned. VCT as the main step taken in several Puskesmas in Pekanbaru on prevention, care, support and treatment services. This study aims to determine the relationship between the quality of VCT services and patient satisfaction at the Sidomulyo Public Health Center, Pekanbaru City. This study used a descriptive correlation research design with a cross sectional approach. The sample in this study were 67 respondents using total sampling technique. The data collection tool used was a questionnaire. Analysis of the data used were univariate and bivariate analysis (chi square). Majority of respondents feel that the quality of service is good, which was 37 people (55,2%) and the level of satisfaction of patients who feel satisfied was 35 people (52,2%). The results of the chi square test showed that there was a relationship between the quality of VCT services and patient satisfaction at the Sidomulyo Public Health Center, Pekanbaru City with p value (0.000) < alpha (0,05). There is a relationship between the quality of VCT services and patient satisfaction at the Sidomulyo Public Health Center, Pekanbaru City.